Islam dan Wanita - Haji Hassan, Abdullah Alwi (Jurnal Usuluddin, 1996)
Islam, as al-Din which connotes it as a complete way of life, touches also in its teaching on women and their status and roles in an Islamic Society. This religion gives an ample opportunities to women to develop their own capabilities in order to play their roles in the society effectively, whether as a wife, mother, professional worker and so on. Islam allows women to have their own rights in the society, namely the right of education, expression property ownership and so forth. They are equal with men in front of God as a Muslim with their own deeds and personal status as the servants of God. An equality between them in Islam does not mean they have the same rights according to their own nature as it is created by God.